LncRNA LINC01134 Contributes to Radioresistance in Hepatocellular Carcinoma by Regulating DNA Damage Response via MAPK Signaling Pathway - Wang, Zhiyi; Wang, Xinxing; Rong, Zhonghou; Dai, Longfei; Qin, Chengkun; Wang, Shikang; Geng, Wenmao (Frontiers in Pharmacology, 2022)
Hepatocellular carcinoma (HCC) is a highly mortal cancer which could be treated by radiotherapy. DNA damage response (DDR) is a vital factor affecting cancer development after radiotherapy. Long non-coding RNAs (lncRNAs) have been revealed to regulate DNA damage response and repair in cancer cells. Nevertheless, the function of long intergenic non-protein coding RNA 1134 (LINC01134) has not been explored in DDR. In this study, we targeted at digging into the function of LINC01134 in DDR and explore the underlying mechanism in HCC cells. RT-qPCR was employed to measure LINC01134 expression, and we found LINC01134 was significantly up-regulated in HCC cells. Functional analysis suggested that LINC01134 depletion attenuated radio-resistance of HCC cells by facilitating DNA damage. In vivo assays demonstrated LINC01134 depletion hindered HCC tumor growth. Mechanism assays unveiled LINC01134 sequestered microRNA-342-3p (miR-342-3p) and recruited insulin like growth factor 2 mRNA binding protein 2 (IGF2BP2) protein to modulate mitogen-activated protein kinase 1 (MAPK1) expression, consequently activating MAPK signaling pathway. Rescue assays validated the LINC01134/miR-342-3p/MAPK1 axis in the radio-resistant HCC cells. In conclusion, LINC01134 might be identified to be a useful biomarker for the therapy of HCC.